Development of Specific DNA Barcodes for the Dinophyceae Family Kareniaceae and Their Application in the South China Sea - Zhang, Weiqian; Zhang, Qingchun; Smith, Kirsty F.; Qiu, Limei; Liu, Chao; Yin, Xiaoting; Liu, Qing (Frontiers in Marine Science, 2022)
Species from the family Kareniaceae (Dinophyceae) frequently cause harmful algal blooms (HABs), seriously threatening ecological and human safety, and aquaculture activities in coastal waters worldwide; however, due to their small size, similar morphology, and low abundance during non-bloom periods, the species diversity of this family is not well understood. By comparing the commonly used molecular markers, the Internal Transcribed Spacer (ITS) region was found to have an appropriate mutation rate to distinguish three of the most common genera (Karenia, Karlodinium, and Takayama) within the Kareniaceae family and different geographical strains of Kareniaceae. Therefore, one pair of specific primers targeting the ITS region of Karenia, and the other pair of primers specific to the genera Karlodinium and Takayama, were designed, and their specificity was tested using 17 strains of Kareniaceae species and 15 non-target species. The results showed that the representative Kareniaceae species could be successfully detected even with a low input of DNA template (down to 3.2 pg). The molecular markers were used as DNA barcodes and tested with two samples from the South China Sea (SCS) by high-throughput sequencing. With a hit rate of (62.4%-96.9%), the barcodes could well realize the specific detection of Kareniaceae species. Analysis of the sequences identified as Kareniaceae species revealed a high diversity and the existence of unreported Kareniaceae species in the SCS. In conclusion, the newly developed molecular barcodes specifically detected Kareniaceae species in the field and are expected to provide technical support for the effective warning and monitoring of Kareniaceae HABs.